ANALISIS KEMAUAN MASYARAKAT DALAM MEMBAYAR TARIF AIR MINUM PDAM SEKTOR RUMAH TANGGA DI KOTA BANDA ACEH - Asrizal Asrizal; Sofyan Syahnur; Muhammad Nasir (Syiah Kuala University, 2018)
AbstractThis explanatory quantitative research aims to determine the factors that affect the Willingness to pay on tariffs at the Regional Water Supply Company (PDAM) Tirta Daroy Banda Aceh. The data used in this research are primary data that obtain from population and the research sample in PDAM Tirta Daroy work area. The sampling technique use in this study was the probability sampling – simple random sampling, the method applying by choosing some of the populations in certain way, so all the population have the same opportunity to be selected or taken. Data were analysed using statistical test - structural equation modelling (SEM) AMOS (analysis of moment structure) which is by doing Confirmatory Factor Analysis (CFA) first. The result of this study show that Willingness to pay (WTP) influenced by customer satisfaction and the regulation, Willingness to pay (WTP) does not affected by the Promotion, customer satisfaction is not influenced by customer education level, customer satisfaction and promotion is influenced by existing regulations / policies, while there is no strong relation between education and customer income.